Programa de capacitación docente para fortalecer actitudes psicoafectivas hacia la inclusión de niños y niñas con necesidades educativas especiales en la escuela de educación básica José Ingenieros N°2, Loja 2014- 2015 - Jiménez Mogollón, Luz Irene (2016)
Currently government policies prioritize inclusion; when performing pre-professional practice several problematic, including inclusive education were identified. Therefore titling this work aimed to propose a teacher training program to strengthen psycho attitudes towards inclusion of children with special educational needs. Descriptive, cross-sectional and quasi-experimental design. The inductive, analytic, synthetic, historical, logical, understanding, diagnosis, modeling and statistical deductive method was used. A survey and the scale of teachers' attitudes towards school integration (EAPROF), in a sample of 17 teachers was applied he wanted to work with the entire teaching population because their attitudes are essential in the teaching-learning process. Results: the three dimensions maintain an average level, 88.23% in the affective dimension (feelings of pleasure towards inclusion); 70.58% in the behavioral dimension (accept the standards set by the Ministry of Education but reject ask scheduled teaching units and are addressed by specialists); 64.70% in the cognitive dimension (knowledge about Inclusive Education) (pretest); training program after the three dimensions increase at a high level the 88.23% in the affective dimension; 82.35% in the behavioral dimension and 76.47% in the cognitive dimension (posttest). a moderate positive correlation r = 0.65 is reached. Conclusions: teachers attitudes manifest social commitment to the inclusion; after the intervention improve the attitudes of teachers, the program reached a moderate positive correlation